2011
DOI: 10.1073/pnas.1100572108
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of biological factors on extinction risk in fossil bivalves

Abstract: Biological factors, such as abundance and body size, may contribute directly to extinction risk and indirectly through their influence on other biological characteristics, such as geographic range size. Paleontological data can be used to explicitly test many of these hypothesized relationships, and general patterns revealed through analysis of the fossil record can help refine predictive models of extinction risk developed for extant species. Here, I use structural equation modeling to tease apart the contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 55 publications
10
114
0
Order By: Relevance
“…In addition, among 61 historical extirpations, large body size explained more than half (57%), followed by greater ecological specialization (28%) and small geographic range (7%) [11]. By contrast, in the marine invertebrate fossil record, geographic range size is the only biological characteristic consistently associated with elevated extinction risk [67][68][69]. The influence of other attributes, such as body size and feeding mode, varies according to extinction magnitude, duration, driver, and clade, and few attempts have been made to assess multiple correlates simultaneously [50,[68][69][70].…”
Section: Biological Correlates Of Extinctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, among 61 historical extirpations, large body size explained more than half (57%), followed by greater ecological specialization (28%) and small geographic range (7%) [11]. By contrast, in the marine invertebrate fossil record, geographic range size is the only biological characteristic consistently associated with elevated extinction risk [67][68][69]. The influence of other attributes, such as body size and feeding mode, varies according to extinction magnitude, duration, driver, and clade, and few attempts have been made to assess multiple correlates simultaneously [50,[68][69][70].…”
Section: Biological Correlates Of Extinctionmentioning
confidence: 99%
“…By contrast, in the marine invertebrate fossil record, geographic range size is the only biological characteristic consistently associated with elevated extinction risk [67][68][69]. The influence of other attributes, such as body size and feeding mode, varies according to extinction magnitude, duration, driver, and clade, and few attempts have been made to assess multiple correlates simultaneously [50,[68][69][70]. Differences over time in the correlates of extinction risk might reflect the disproportionate current and historical impacts of exploitation relative to other threats, such as habitat loss, as well as differences between vertebrates and invertebrates, which are the focus of most paleontological analyses.…”
Section: Biological Correlates Of Extinctionmentioning
confidence: 99%
“…Work focused on the Quaternary and Late Neogene has demonstrated that beetles are quite resilient to extinction, owing to their ability to change their geographical distributions in response to climate change [59]. In fact, ecology, morphology and geographical range size [54,60,61] are thought to contribute to extinction risk and in fact, many of these traits may be phylogenetically constrained [62,63]. Focusing on extinction and what life-history characteristics make some beetles more likely to go extinct when compared with other groups of beetles may provide a greater understanding of why polyphagan beetles are so diverse.…”
Section: Penn P Ep Mp P Mp M Lpet T E E E Et T P Pe T T Mt T T T T T mentioning
confidence: 99%
“…Thus, existing studies do not readily allow direct comparisons of past losses of EH with those predicted for anthropogenic extinctions. Although temporal durations of species in the fossil record are more difficult to estimate reliably than those of higher taxa (23), a number of paleontological studies have used fossil species successfully to test important evolutionary and biogeographic hypotheses (21,(51)(52)(53)(54)(55)(56) as well as various aspects of the extinction process (57)(58)(59). With the increasing availability of large, taxonomically standardized paleontological databases, analyses of age selectivity of extinctions at the species level, such as the one undertaken here, are now feasible, especially on regional scales.…”
Section: Discussionmentioning
confidence: 99%